Estimated discharge of microplastics via urban stormwater during individual rain events - Ross, Matthew S.; Loutan, Alyssa; Groeneveld, Tianna; Molenaar, Danielle; Kroetch, Kimberly; Bujaczek, Taylor; Kolter, Sheldon; Moon, Sarah; Huynh, Alan; Khayam, Rosita; Franczak, Brian C.; Camm, Eric; et al. (Frontiers in Environmental Science, 2023)
Urban stormwater runoff is an important pathway for the introduction of microplastics and other anthropogenic pollutants into aquatic environments. Highly variable concentrations of microplastics have been reported globally in runoff, but knowledge of key factors within the urban environments contributing to this variability remains limited. Furthermore, few studies to date have quantitatively assessed the release of microplastics to receiving waters via runoff. The objectives of this study were to assess the influence of different catchment characteristics on the type and amount of microplastics in runoff and to provide an estimate of the quantity of microplastics discharged during rain events. Stormwater samples were collected during both dry periods (baseflow) and rain events from 15 locations throughout the city of Calgary, Canada’s fourth largest city. These catchments ranged in size and contained different types of predominant land use. Microplastics were found in all samples, with total concentrations ranging from 0.7 to 200.4 pcs/L (mean = 31.9 pcs/L). Fibers were the most prevalent morphology identified (47.7±33.0%), and the greatest percentage of microplastics were found in the 125-250µm size range (26.6±22.9%) followed by the 37-125µm size range (24.0±22.3%). Particles were predominantly black (33.5±33.8%), transparent (22.6±31.3%), or blue (16.0±21.6%). Total concentrations, dominant morphologies, and size distributions of microplastics differed between rain events and baseflow, with smaller particles and higher concentrations being found during rain events. Concentrations did not differ significantly amongst catchments with different land use types, but concentrations were positively correlated with maximum runoff flow rate, catchment size, and the percentage of impervious surface area within a catchment. Combining microplastic concentrations with hydrograph data collected during rain events, we estimated that individual outfalls discharged between 1.9 million to 9.6 billion microplastics to receiving waters per rain event. These results provide further evidence that urban stormwater runoff is a significant pathway for the introduction of microplastics into aquatic environments and suggests that mitigation strategies for microplastic pollution should focus on larger urbanized catchments.